Empowering ECCE Educators: Improving Understanding, Skills, and Development of the Independent Curriculum, with Teaching Modules and Learning Media Based on Augmented Reality - Irfan Fauzi Rachmat; Cucu Sopiah; Fakhry Fajrin Kurniawan; Mumun Munawaroh (Dimasejati: Jurnal Pengabdian Kepada Masyarakat, 2023)
This Community Service aims to enhance the understanding and skills of teachers at TK Labschool UMC and Daycare UMC regarding the Merdeka PAUD Curriculum and the development of interactive digital media teaching modules using augmented reality. Conducted as an empowerment-based community service, the activities took place at TK Labschool UMC over an intensive period of 2 months with three training sessions. The method involved the entire teacher population, utilizing purposive sampling techniques. The results indicated an improvement in the understanding of the principles of the Merdeka PAUD Curriculum, the ability of teachers to develop a distinctive curriculum for TK Labschool UMC, and their competence in creating teaching modules and integrating augmented reality technology into the learning process. The conclusion affirms that this community service has successfully empowered teachers, resulting in a positive impact on early childhood education